Representative Democracy: Legislators and their Constituents - Mezey, Michael L. (Rowman & Littlefield Publishers, 2008)
Although we tend to use the terms 'representative democracy' and 'democracy' as synonyms, Michael Mezey maintains that they are not. Democracy means that the people govern; representative democracy means that the people elect others to govern for them. This raises the question of the extent to which representative government approximates democracy-a question that turns on the relationship between representatives and those whom they represent. Mezey reviews the literature on the meaning of representation and its relationship to issues of citizen control. In the empirical sections that follow, he draws on data from the United States Congress and from legislatures outside the United States to discuss the extent to which the composition of a legislature reflects the demography of its nation. The author also examines a legislature's various political and economic interests and the extent to which representatives are responsive to specific requests for assistance from their constituents and to constituent opinions on public policy questions. He further looks at the effect that interest groups, political parties, and election systems have on the relationship between representatives and their constituents. Finally, Mezey addresses the criticisms that have been leveled against representative institutions: that they are slow to act, inefficient and uninformed when they do act, that they are too inclined to do what is popular rather than what is necessary and, conversely, that their members are too removed from the opinions of their constituents and therefore unfaithful to their democratic obligation to respond to the wishes of those whom they represent. Rich in thoughtful analysis, Representative Democracy incorporates normative, empirical and comparative perspectives on representation. It is perfectly suited for use in an upper-level course on the legislative process or Congress.